Occurrence of overuse injuries in elite Swedish athletics - A prospective cohort study over one athletics season - Lundberg Zachrisson, A.; Desai, P.; Karlsson, J.; Grau, S. (Translational Sports Medicine, 2020)
The incidence proportion and severity of overuse injuries (OIs) in elite athletics are still unclear due to methodological limitations of prior studies. The aim was to prospectively measure OI incidence proportion, severity, and anatomic location during a complete Swedish elite athletics season. Seventy-five male and female elite athletes between 18 and 32 years of age, competing in either middle- and long-distance running, sprint, jumping, or throwing events were recruited. A medical professional diagnosed injuries during a physical examination. All injuries were classified as gradual or sudden onset incident injuries due to overuse. An athlete was considered injury free after reporting full return to training in their training documentation. The OI incidence proportion was 72.4% (95% CI: 60.8%, 84%), with 71 recorded injuries. Most injuries were severe, with 38% of them being moderately serious (8-28 days) and 36.6% serious (>28 days-6 months). The most common injury location was the thigh/hip at 41% followed by the foot/shank at 39%. The incidence proportion and severity of OIs were higher when medical professionals evaluated each athlete who developed symptoms, compared to self-reporting athletes. Future research should evaluate possible risk factors for OIs to try to lower the OI incidence proportion.